SEISMIC UPGRADING OF RC COUPLED SHEAR WALLS: STATE OF THE ART AND RESEARCH NEEDS (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Coupled shear walls are one of the most efficient structural systems for resisting lateral loadings due to wind and earthquakes. Their performance relies predominantly on the coupling beams, which must be appropriately designed and detailed to provide enhanced ductility and energy-absorption capacity. Many existing buildings with coupled shear walls were designed according to previous generations of codes and standards. Therefore, they are not up to modern, more stringent seismic codes and standards. Retrofitting coupling beams to improve their seismic performance can be a viable and cost-effective option. The objective of this paper is threefold: (i) to identify the deficiencies of existing coupling beams; (ii) to present a literature review of different techniques and methods for retrofitting coupling beams to enhance their seismic performance; and (iii) to highlight the advantages and disadvantages of these techniques. In addition, some strengthening techniques used for beam-wall joints, which play an important role in providing shear capacity for coupled shear walls, are also presented. Finally, research needs for a new and practical retrofit method with FRP sheets to improve the seismic performance of existing coupled shear walls are outlined.